Staircase of the temple - Temples of India Project Team (Jio Institute, 2024)
Stairs leading to the temple, situated on an elevated area. There are stone platforms or benches placed on both sides of the steps to provide a sitting place for the devotees. At the third stone bench, on both sides of the stairs, one can notice a stone tablet of Jaipur Circle, Archaeological Survey of India (ASI), indicating it to be a National Protected Site.